Climate policies and economic growth - Kari E. O. Alho (The Research Institute of the Finnish Economy (ETLA), 2006)
A Climate Agreement, like the one reached in Kyoto in 1997, on reducing greenhouse gas emissions may have important effects on the global and the national economies. The aim of this paper is to make some basic numerical evaluations of the economic effects of climate policies, imposing a ceiling on the use of energy input in production in a single economy. First, we make an evaluation under immobile and internationally mobile domestic factors of production, and infer how much international factor mobility, so-called carbon leakage, can magnify the adverse effects. Next, we introduce optimal endogenous growth, so that environmental policies can potentially lead to the introduction of less-polluting energy technologies. The general conclusion of this is that induced R&D in less-polluting energy technologies is likely to reduce the economic burden of climate policies only marginally. Under an internationally tradable emissions permit scheme, however, the endogenous technical change reacts quite vigorously to the price of the pollution right. Finally, we solve for the optimal subsidy to R&D in clean energy technology in a market economy, and find it to be quite sizeable.
Keywords: Q43; Q48; 330; Climate policies; economic growth; R&D; Klimaschutz; Wirtschaftswachstum; Energieforschung; Energietechnik; Emissionshandel; Wirkungsanalyse; Theorie